2009
DOI: 10.1002/jcp.21843
|View full text |Cite
|
Sign up to set email alerts
|

Expression of angiogenic regulators, VEGF and leptin, is regulated by the EGF/PI3K/STAT3 pathway in colorectal cancer cells

Abstract: Both leptin and vascular endothelial growth factor (VEGF) are growth and angiogenic cytokines that are upregulated in different types of cancer and have been implicated in neoplastic progression. Here we investigated the molecular mechanism by which leptin and VEGF expression are regulated in colon cancer by epidermal growth factor (EGF). In colon cancer cell line HT-29, EGF induced the binding of signal transducer and activator transcription 3 (STAT3) to STAT3 consensus motifs within the VEGF and leptin promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 39 publications
3
28
0
Order By: Relevance
“…The ability to suppress the function of T-cell and NK cells provides the most effective way of identifying MDSCs [96]. The expansion of MDSCs is influenced by pro-myelopoetic factors produced by colorectal carcinoma cells [104], such as stem cell factor (SCF), M-CSF, PGs, IL-6, GM-CSF, and VEGF [105], while the activation factors produced by MDSCs are produced by both activated T-cells and stromal cells and include IFN-γ, TLR ligands, IL-4, IL-13, and TGF-β. The suppressive effect of MDSCs has been associated with the metabolism of L-arginine, a substrate for the two key enzymes, arginase-1 and iNOS (which generates NO).…”
Section: Myeloid-derived Suppressor Cellsmentioning
confidence: 99%
“…The ability to suppress the function of T-cell and NK cells provides the most effective way of identifying MDSCs [96]. The expansion of MDSCs is influenced by pro-myelopoetic factors produced by colorectal carcinoma cells [104], such as stem cell factor (SCF), M-CSF, PGs, IL-6, GM-CSF, and VEGF [105], while the activation factors produced by MDSCs are produced by both activated T-cells and stromal cells and include IFN-γ, TLR ligands, IL-4, IL-13, and TGF-β. The suppressive effect of MDSCs has been associated with the metabolism of L-arginine, a substrate for the two key enzymes, arginase-1 and iNOS (which generates NO).…”
Section: Myeloid-derived Suppressor Cellsmentioning
confidence: 99%
“…VEGF is believed to be the principal growth stimulatory factor for tumor-related angiogenesis. constitutive activation of Stat3 is able to up-regulate VEGF-a expression in human pancreatic and colorectal cancer cells (12,13).…”
mentioning
confidence: 99%
“…Earlier studies have reported that pSTAT3 promotes tumor angiogenesis by acting as a direct transcriptional activator of VEGF and mediates expression of genes related to tumor growth and metastasis [6]. Recently, Cascio and co-investigators supported this evidence in colon cancer cells by demonstrating the binding of STAT3 to the promoter of VEGF [47]. Elevated levels of MMP-7 mRNA was detected in colorectal tumor tissues with activated form of STAT3 [3].…”
Section: Discussionmentioning
confidence: 93%